Business Law Ethics in the Perspective of Muhammadiyah Values: The Challenge of Applying Business Ethics in the Modern Era - Resmaya Agnesia Mutiara Sirait; Anita Yuliastini; Thadeus Yus; Annurdi (Jurnal Hukum Ekonomi Syariah, 2025)
The rapid development of information and communication technology in Indonesia's business sector has made the existing business sector increasingly complex and competitive. The application of strong ethics is very important to maintain integrity and trust among business actors, considering that the challenges faced by business actors are also based on Islamic principles. The perspective of Muhammadiyah values, which are based on Islamic teachings that prioritize justice and ethics, has an important point in making a significant contribution to overcoming the challenges that exist in business ethics today. This study aims to identify and analyze the principles of business law ethics from the perspective of Muhammadiyah values, exploring the challenges faced in the application of business ethics from the perspective of Muhammadiyah values in the modern era. This research uses a literature study research method, which is a series of activities related to collecting library data, reading and recording, and managing research materials. The context of this research is important to examine in order to strengthen the position of business ethics from the Muhammadiyah perspective.